A Military History of Modern China, 1924-1949 - Liu, F. F. (Frederick Fu), 1919- (New Jersey Princeton University Press, 1956)
Princeton University Press, 1956, Very good., Text clean. Private bookplate. 312 pages. [Modern China, Chinese History, Military History] Out-of-print and antiquarian booksellers since 1933. We pack and ship with care.
Include Bibliography and Index
Keywords: China -- History, Military -- China -- Military History